ALAM TAKAMBANG JADI GURU: MENELISIK FALSAFAH PENDIDIKAN BERBASIS KEARIFAN LOKAL DI MINANGKABAU - Dadi Satria; Wening Sahayu (Vokal: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2022)
This study aims to reveal the meaning and reality of the philosophy of "Alam Takambang jadi Guru" as a view of life of the Minangkabau people and the implications and efforts to maintain this philosophy through literature review. This research method is qualitative research using descriptive methods. This research is naturalistic because it is carried out in natural conditions through social observation and literature review based on the latest theories and research results. Based on the results of the analysis, it can be concluded that several things, namely (1) the philosophy of "Alam Takambang Jadi Guru" has an important meaning for the Minangkabau community that nature is not just a place to live and develop, but as a source of lifelong learning and nature as a gift from God Almighty, (2 ) the philosophy of "Alam Takambang jadi Guru" has implications for both formal and non-formal education in the life of the Minangkabau community, and (3) efforts to maintain the philosophy of "Alam Takambang jadi Guru" can be carried out through culture experience and culture knowledge.